The integration process as a determinant of intra-industry trade - Lorena Skufliæ (European Regional Science Association (ERSA), 2005)
Trade structure is usually defined as inter or intra-industrial type. The pattern of production and trade that emerges after opening the economies of transition is partly driven by relative factor prices and endowment and partly by economies of scale and scope, but much depends on historical experiences. The first determinancy will lead to the increasing inter-industry trade, so the country which has labour force exports labour-intensive products and imports capital-intensive products because capital is its rare factor. The more dissimilar are countries endowment, the greater the volume of inter-trade will be. This concept of trade is based on Heckser-Ohlin theorem. The second factor will generate intra-industry trade, the exchange of similar manufactured goods, with companies specialized in different varities of similar goods. Economic theory predicts that the volume of intra-industry trade depends of two groups of determinants; first group is related to country and second to the industry. Determinants relate to the country are: level of the economic development, size of the market, distance between countries, trade orientation, economic integration and trade barriers. In this paper will be analyze some of before mentioned determinants. During research, it will be used the Grubel-Lloyd index to calculate the intensity of intra- industry trade at the 4-digit SITC levels to determine the relative importance of IIT as opposed to inter-industry trade in the trade exchange between Croatia and EU and Slovenia and EU. IIT would be estimated for whole trade and across industries on the case of Croatia and Slovenia. A time series approach would be used to estimate any trend in the ratio of intra industry trade to total trade in relation to the EU. These analyze has aim to consider how trade has changed in the period of trade liberalization and including in integration process. On the basis of collected statistical data,it will be calculate the intra-industry trade index, and inter-industry index and also analyze if there is vertical or horizontal intra-industry trade. According to the economic theory removal of trade barriers through bilateral and multilateral negotiations has positive impacts on IIT but the results do not proof hypo these especially in the case of Croatia, very IIT decreases as integration process goes on.
Keywords: 330